Ontology and epistemology in management research: An islamic perspective. - Mohammed Kamil, Naail (2011)
From the Western value system, two kinds of ontological and epistemological standpoints are characterized in Management and Social Sciences research; realist ontology and subjectivist ontology or objectivist epistemology and subjectivist epistemology. The kind of ontology and epistemology a researcher commits to has inherent effects towards the researcher’s way of contributing new knowledge. This short communication attempts to contribute new knowledge to the literature of philosophical standpoints in management research by discussing the ontological and epistemological stances with respect to Islam. It was shown that the Islamic viewpoint of ontology and epistemology is in the middle side between realist - subjectivist ontology and between objectivist – subjectivist epistemology. This stance of Islam on ontology and epistemology as elaborated in the Qur’an and the tradition of the Prophet Muhammad (peace be upon him) increases the resilience with which knowledge is contributed in a holistic manner regardless of social, cultural or political backgrounds.